«EVERY WRITER CREATES THEIR OWN PRECURSORS»: MARIE DARRIEUSSECQ ON PAULA MODERSOHNBECKER - Álvarez Gavela, Ariadna (Filanderas, 2021)
The French novelist Marie Darrieussecq published in 2016 a biography of the German painter Paula Modersohn-Becker, known for having been the first woman to portray herself naked. This article introduces this text in an interpretive struggle that has marked the reception of Modersohn-Becker’s work in feminist criticism from the 1970s to the present. Contrasting the vision that Darrieussecq offers of the German artist with that of art historians such as Linda Nochlin, Roszika Parker or Griselda Pollock, the reasons that the French author uses to present Modersohn-Becker as a pioneering artist in the developement of an artistic language that is articulated in feminine are identified and analyzed. In addition, a hypothesis that runs through the article is deployed: Darrieussecq constructs Paula Modersohn-Becker as a transdisciplinary referent, a precoursor who, beyond her scope of expression, the plastic, was able to expand the boundaries of female self-representation.
Keywords: Biography; Female self-representation; Nude; Woman; Nature; Female artists